Self-Regulation of Soil Enzyme Activity and Stoichiometry under Nitrogen Addition and Plastic Film Mulching in the Loess Plateau Area, Northwest China - Meixia Liu; Menglu Wang; Congwei Sun; Hui Wu; Xueqing Zhao; Enke Liu; Wenyi Dong; Meiling Yan (Agriculture, 2023)
Soil extracellular enzyme activity (EA) and its eco-enzyme stoichiometric ratio (ES) are extremely sensitive to environmental change. This study aimed to clarify the change law of EA and ES in soil with different nitrogen addition levels under plastic film mulching, and to optimize the application amount of nitrogen fertilizer that was used. Based on the location experiment of plastic film mulching fertilization that has been ongoing since 2015, soil samples were collected from different depths (0–10 cm, 10–20 cm and 20–30 cm) during the harvest period of spring maize in October 2021. Four soil extracellular enzyme activities (β-1,4 glucosidase (βG), β-1, 4-N-acetylglucosidase (NAG), leucine aminopeptidase (LAP) and alkaline phosphatase (AP)) involved in soil carbon (C), nitrogen (N) and phosphorus (P) cycling at different nitrogen application levels (0, 90, 150, 225 and 300 kg·hm−2) were studied under two planting patterns of no plastic film mulching (LD) and plastic film mulching (PM). The latest discovery of this study is that the activities of soil EA involved in the cycling of soil carbon C, N and P are similar in different soil depths (0–10 cm, 10–20 cm and 20–30 cm). Both EC:P and EC:P in the soil in this area are less than 1:1, indicating that the soil is limited by N and P. Comprehensive analysis showed that a nitrogen application level of 225 kg·hm−2 was beneficial to the balance of soil nutrients and the improvement of soil EA at harvest. At the same time, PM can effectively improve the soil EA and is more conducive to the balance of soil nutrients. Redundancy analysis (RDA) showed that EA and ES were strongly correlated with pH, soil organic carbon (SOC), total nitrogen (TN) and total phosphorus (TP). Most importantly, this study revealed that the activity of extracellular enzymes in arid and semi-arid areas was constantly self-regulated with the addition of nitrogen, which provided theoretical and technical support for the efficient use of nitrogen under the condition of plastic film mulching.